Tangshenning Attenuates High Glucose-Induced Podocyte Injury via Restoring Autophagy Activity through Inhibiting mTORC1 Activation. (28th June 2022) - Xu, Jiayi; Shan, Xiaomeng; Chen, Chunwei; Gao, Yanbin; Zou, Dawei; Wang, Xiaolei; Wang, Tao; Shi, Yimin
Abstract : Diabetic nephropathy (DN) is a microvascular complication of diabetes mellitus (DM) and the most common cause of death in diabetic patients. DN progression is associated with podocyte damage due to reduced autophagy caused by mTORC1 activation. Tangshenning (TSN) has been shown to reduce proteinuria, protect renal function, and reduce podocyte damage. Still, the effect of TSN on the autophagic activity of podocytes remains unclear. Herein, in vitro experiments using a high glucose-induced podocyte injury model were performed. Results showed that TSN treatment enhanced the weakened nephrin expression and autophagic activity of podocytes and inhibited the mTORC1 pathway (p-mTOR, mTOR, p-p70S6K, p70S6K, ULK1, and 4EBP1) under high glucose conditions. Furthermore, the mTORC1 activator (siRNA-TSC2) partially inhibited the above beneficial effects of TSN, suggesting that mTORC1 was the target of TSN to regulate autophagy. In summary, TSN reduces podocyte damage induced by high glucose via inhibiting mTORC1 pathway and downstream targets and restoring podocyte autophagy.